Why do academicians share knowledge? A study of higher education institutions in India - Ahmad, Asad; Alam, Md Sarwar; Kirmani, Mohd Danish; Madsen, Dag Øivind (Frontiers in Psychology, 2023)
Purpose-Indian higher education institutions are diverse in nature, there; there are institutions with good infrastructure and resources as well as institutes that who stands nowhere in terms of resources and infrastructure. Keeping in mind the relevance of knowledge sharing in the academic institutions, the researchers in the present study have tried to find out factors determining the knowledge sharing behavior of the academicians of different institutes in India.The researchers in the present work have expanded on the extant research by demarcating factors that affect knowledge sharing behaviour of the academicians. A structured questionnaire was shared through e-mail, and social media groups, and as well asa snowball approach was used to reach out to maximum number of respondents.Findings-The present study offers an integrated and extended TRA and TPB theoretical model, augmenting it with constructs such as like motivation and the opportunity to share knowledge adapted from prominent related research findingsstudies. The findings of this research provide theoretical as well as practical suggestions in determining and explaining knowledge sharing behaviour of academicians.The researchers in the present study have tried to present a shorter and more reliable scale which that can be used to assess the behavioural intentions of the academicians to share knowledge.